Exploring the Indonesian Maritime Art toward Appreciation of Coastal Literacy - Heriyawati, Yanti; Wita, Afri (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
There are many global literatures of art appreciation, but only few of them focus on maritime art appreciation. Filling the vacancy requires study of how the community or public values maritime art works in the context of coastal community’s literacy. This paper aims to show appreciation of Indonesian maritime art works. It presents the results of maritime art appreciation through Focus Group Discussion (FGD). The participants consisted of academician, governmental official, artist, creator, community, kiyai, and student. The maritime art works which are appreciated were “Segara Garam’ and “Tasbih Pesisir”. They are considered as natural and virtual art works. Respondents’ insight, knowledge, and experience showed varied perceptions. Participants with maritime culture background were quite expressive in expressing the importance of local wisdom values of the coastal community. Meanwhile the respondents without maritime culture background paid more attention on artistic and aesthetic aspects, instead of on meaning. Sociocultural difference influenced how they appreciated and produced the knowledge of maritime culture. Respondents’ cognition and affective abilities show varied interpretation, perception, and meaning of art values. Their experience of appreciation showed the importance of perception of maritime art in actualizing local genius. The appreciation of maritime art was performed to improve people’s awareness of strengthening maritime culture literacy.